Expanding the genetic and phenotypic relevance of KCNB1 variants in developmental and epileptic encephalopathies: 27 new patients and overview of the literature. Issue 1 (4th October 2019) - Bar, Claire; Barcia, Giulia; Jennesson, Mélanie; Le Guyader, Gwenaël; Schneider, Amy; Mignot, Cyril; Lesca, Gaetan; Breuillard, Delphine; Montomoli, Martino; Keren, Boris; Doummar, Diane; Billette de Villemeur, Thierry; et al.
Abstract: Developmental and epileptic encephalopathies (DEE) refer to a heterogeneous group of devastating neurodevelopmental disorders. Variants in KCNB1 have been recently reported in patients with early‐onset DEE. KCNB1 encodes the α subunit of the delayed rectifier voltage‐dependent potassium channel Kv 2.1. We review the 37 previously reported patients carrying 29 distinct KCNB1 variants and significantly expand the mutational spectrum describing 18 novel variants from 27 unreported patients. Most variants occur de novo and mainly consist of missense variants located on the voltage sensor and the pore domain of Kv 2.1. We also report the first inherited variant (p.Arg583*). KCNB1 ‐related encephalopathies encompass a wide spectrum of neurodevelopmental disorders with predominant language difficulties and behavioral impairment. Eighty‐five percent of patients developed epilepsies with variable syndromes and prognosis. Truncating variants in the C‐terminal domain are associated with a less‐severe epileptic phenotype. Overall, this report provides an up‐to‐date review of the mutational and clinical spectrum of KCNB1, strengthening its place as a causal gene in DEEs and emphasizing the need for further functional studies to unravel the underlying mechanisms. Abstract : KCNB1 encodes the α subunit of the delayed rectifier voltage‐dependent potassium channel Kv 2.1. In this mutation update, we provide an up‐to‐date review of the mutational and clinical spectrum of the KCNB1 encephalopathy and report 18 novel variants.